Biomimetic Three-Dimensional (3D) Scaffolds from Sustainable Biomaterials: Innovative Green Medicine Approach to Bone Regeneration - Yashaswini Premjit; Merin Lawrence; Abhishek Goyal; Célia Ferreira; Elena A. Jones; Payal Ganguly (Journal of Functional Biomaterials)
Bone repair and regeneration following an injury still present challenges worldwide. Three-dimensional (3D) scaffolds made from various materials are used for bone tissue engineering (BTE) applications. Polymers, minerals and nanotechnology are now being used in combination to achieve specific goals for BTE, including the delivery of antimicrobials through the scaffolds to prevent post-surgical infection. While several materials are utilised for BTE, natural polymers present a unique set of materials that can be manipulated to formulate scaffolds for BTE applications. They have been found to demonstrate higher biocompatibility, biodegradability and lower toxicity. Some even naturally mimic the bone microarchitecture, providing inherent structural support for BTE. Natural polymers may be simply classified as those from plant and animal sources. From both sources, there are different types of proteins, polysaccharides and other specialised materials that are already in use for research in BTE. Interestingly, these have the potential to revolutionise the field of BTE with a sustainable approach. In this review, we first discuss the different natural polymers used in BTE from plant sources, followed by animal sources. We then explore novel materials that are aimed at sustainable approaches, focusing on innovation from the last decade. In these sections, we outline studies of these materials with different types of bone cells, including bone marrow mesenchymal stromal cells (MSCs), which are the progenitors of bone. We finally outline the limitations, conclusions and future directions from our perspective in this dynamic field of polymers in BTE. With this review, we hope to bring together the updated existing knowledge and the potential future of innovation and sustainability in natural polymers for biomimetic BTE applications for fellow scientists, researchers and surgeons in the field.